Determination of Ketotifen Fumarate in Syrup Dosage Form by High Performance Liquid Chromatography - Ali Salih, Mohammed; Fattah Aziz, Dlivan; Ibrahim Ali, Salar (Kurdistan Journal of Applied Research, 2020)
The goal of the current study was to establish and authenticate an isocratic reverse-stage High-Performance Liquid Chromatography (HPLC) method for quantifying ketotifen fumarate (KF) in pharmaceutical liquid dosage compositions. Easy, quick, accurate, exact, and accurate reverse-stage high-performance liquid chromatography was advanced for the simultaneous assessment of ketotifen fumarate in the liquid syrup dosage type. The HPLC system using isocratic elution method with reverse-phase Inertsil ODS-(250 mm × 4.6 mm, 3 ?m) column was detected by ultraviolet absorbance at 297 nm with no interference from widely using excipients, the mobile phase (A) is a mixture of triethylamine and water (175 ?l in 500 ml of water), and the mobile phase (B) is a mixture of triethylamine and methanol (175 ?l in 500 ml of methanol) at a flow rate of 1.5 mL/min (mobile phase A 40 %:mobile phase B 60%) at column temperature using 40 ° C, the retention time for ketotifen fumarate was 6.4±0.5 min. The concentration curves were linear in the range of 10.0 to 35.0 ?g / ml (R2 = 0.9999). The developed method was tested for the specificity, precision, linearity, precision, reliability, robustness, and consistency of the solution. The regeneration of ketotifen fumarate in formulations was found to be 99.75 %, 99.91 %, and 100.05 % respectively. The percent RSD for percent recovery was found to be 0.21 and 0.17 and 0.10 for ketotifen fumarate. In the conclusion, the suggested technique was successfully used for the quantitative determination of ketotifen fumarate in formulations.